Development of Digital Teaching Materials to Improve Students' Understanding of Concepts in Physics Subjects - Endasyari Juliarti; Rosane Medriati; Eko Risdianto (CV. Media Inti Teknologi, 2024)
The results of interviews with several students and show that there are still many students who have difficulty in understanding concepts in dynamic fluids. Therefore, researchers conduct research that aims to develop digital teaching materials, namely e-modules using the Canva application on the subject of dynamic fluids. This research was carried out using the Research & Development method. The design validity stage involves 3 subjects (two expert judges and one practitioner) involved to assess the feasibility of the material, the design of e-modules, the feasibility of Indonesian language and the feasibility of good and correct media. Feasibility assessment by experts using validation sheets. The trial phase involved 102 students from three schools, namely SMAN 4 Kota Bengkulu, SMAN 5 Kota Bengkulu, and SMAN 9 Kota Bengkulu. Assessment of the attractiveness of the e-module using descriptive analysis assisted by Microsoft Office Excel 2007. The results showed that the feasibility score by the three experts with an average percentage in the content aspect was 92.70%, in the presentation aspect of 91.67%, in the aspect of 98.33, in the media aspect of 97.91%. The response of students with an average percentage of SMAN 4 Bengkulu City 82.22% is in the very good category, SMAN 5 Bengkulu City with an average percentage of 85.01% is in the very good category, SMAN 7 Bengkulu City with an average percentage of 89.65% is in the very good category. So it can be concluded that the e-module using the Canva application produced in this study is considered suitable for use in dynamic fluid learning.